Voltammetric Behavior of nitrofurazone at highly boron doped diamond electrode - Juliao, M; Almeida, E; Scalea, L; Ferreira, N; Compton, R; Serrano, S (2005)
The electrochemical behavior of nitrofurazone (NFZ) at a highly boron doped diamond (BDD) electrode was studied in Britton-Robinson (BR) buffer using cyclic voltammetry. NFZ was directly reduced to the amine derivative (RNH 2) in the pH range of 2.0 to 4.0 in a process involving six (6.0 ± 0.4) electrons and six protons. In the range of pH 7.0 to 12 and, predominantly aqueous medium, the reduction step split into its two components: the reduction of NFZ to the radical anion (RNO2-) and reduction of RNO2- to hydroxylamine derivative (RNHOH) in processes involving one and three (3.1 ± 0.1) electrons, respectively. On the anodic scan of the voltammograms and at pH 8.0, the oxidation of the hydroxylamine to the nitroso derivative (RNO), was observed in a process involving 2 (1.7 ± 0.2) electrons and 2 protons. In addition and unreported in the literature on any electrode material, was the detection of a new oxidation peak at pH > 8.0, which was observed regardless of whether NFZ had been previously reduced or not. The calculation of n, number of electrons, involved in each electrochemical step was satisfactorily accomplished using the Randles-Sevcik equation. © 2005 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.